Substituted 4-hydroxy-1, 2, 3-triazoles: synthesis, characterization and first drug design applications through bioisosteric modulation and scaffold hopping approaches1. Issue 7 (8th July 2015) - Pippione, Agnese C.; Dosio, Franco; Ducime, Alex; Federico, Antonella; Martina, Katia; Sainas, Stefano; Frølund, Bente; Gooyit, Major; Janda, Kim D.; Boschi, Donatella; Lolli, Marco L.
<x xml:space="preserve">Abstract</x> The hydroxytriazole system is here analysed and used to modulate acidic moieties present in lead compounds.